Veiksmažodžio matyti komplementų tipai: formos ir reikšmės sąveika - Usonienė, Aurelija (Baltistica, 2001)
COMPLEMENTATION OF THE VERB matyti (‘SEE’): INTERACTION OF FORM AND MEANINGThe paper sets out to disclose the workings of syntax-semantics interaction using as an example the analysis of complementation of the Lithuanian verb matyti (‘see’). The focus is on the structural differences of basic types of complements and their impact upon the meaning of the matrix verb. Following Lyons’ classification of entities (Lyons 1977,1991) and the typology of perception-verb complements based on the hierarchical structure of the clause developed by Dik and Hengeveld (1991), the present analysis suggests considering the feature of simultaneity to be crucial in distinguishing between MP and IPSoA constructions among non-finite (participial/gerundial) complements of this verb of seeing in Lithuanian. Types of complements containing the forms of the Lithuanian participle and gerund marked for the future or past tense found in matyti (‘see’) complementation denote propositions (3rd-order entities). The given MP constructions can be also said to express an evidential qualification. The meaning extension of matyti (‘see’) is the same as that of see in English, from direct to indirect or mental perception, and the ‘cognitive format’ of expression becomes fully acceptable to the verb. A few present tense personal forms like matot(e) (‘see’2ndPlPrs), matome (‘see’1 PlPrs), matau (‘see’lSgPrs) that function parenthetically preserve an evidential qualification and thus, can be regarded as undergoing pragmaticalization (Aijmer 1997), while the infinitive form matyti (‘see’ Inf) undergoes grammaticalization: its shortened form matyt (‘evidently’) develops into a parenthetical word with the modal meaning of epistemic possibility/uncertainty.
Keywords: lietuvių kalba; veiksmažodis; matyti